Cognitive and Linguistic Effects of Working Memory Training in Children With Corresponding Deficits - Pauls, Laura J.; Archibald, Lisa M. D. (Frontiers in Education, 2022)
Working memory training has been found to result in improvements on tasks similar to those involved in the training (near transfer) but show limited impact on everyday skills such as language or academic abilities (far transfer). Previous research has largely focused on those with a broad range of skills, and examined group level responses. This study uses a single subject design to examine the effect of working memory training on both working memory and related domains in children with working memory impairment. Seven children (8–11 years old) with a working memory impairment completed 20 sessions of computerized working memory intervention. Data revealed near transfer for all participants. Evidence of far transfer to improvements in language, reading, or math was observed for approximately half of the participants on individual measures. Three participants showed convincing but modest training effects across multiple measures. A combination of factors appeared to influence far transfer including age, training intensity, and baseline measures.